2004
DOI: 10.1002/j.0022-0337.2004.68.9.tb03844.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in a Dental School Patient Population

Abstract: Patient records were retrospectively reviewed to investigate the incidence of hypertensive patients seen at a U.S. dental school. This research was conducted to create an awareness of the current problems in diagnosing and treating hypertensive patients in the dental environment. Nine hundred and seventy-six records of patients seen between January 1, 1999 and January 1, 2000 were reviewed. Five hundred records that met specific study criteria related to health history, medications used, recorded blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1
4

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
1
10
1
4
Order By: Relevance
“…In the present study, 66% of those with HBP were not aware of their condition prior to their dental visits. This is higher than that reported among dental patients in the US and in Japan (12, 13), which could be an indication of the lower health awareness in the present sample. Moreover, almost half of those with history of hypertension had elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…In the present study, 66% of those with HBP were not aware of their condition prior to their dental visits. This is higher than that reported among dental patients in the US and in Japan (12, 13), which could be an indication of the lower health awareness in the present sample. Moreover, almost half of those with history of hypertension had elevated blood pressure.…”
Section: Discussioncontrasting
confidence: 87%
“…In a recent study in Saudi dental patients, history of hypertension was reported by only 6.7% of the studied sample and this lower prevalence was attributed in part to the possibility that some patients may have undiagnosed hypertension (11). In two studies among dental school patients in the US and in Japan, 49% and 20%, respectively, of persons with high blood pressure (HBP) were not aware of their condition prior to their dental visit (12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, measures of provider–patient interaction and its perceived quality are absent from these surveys, although patients drawn to the dental school setting may find these qualities more important than patients who seek care in a conventional dental setting [8]. While the attributes of dental school patients have been previously described, the studies have focused on specific groups, such as those with mental illness, substance abuse disorders, cancer, or hypertension [9,10,11,12]. Income and enrollment in insurance have previously been documented to predict the receipt of preventive dental services in the dental school setting; however, to our knowledge, this is the first study assessing the factors that lead dental school patients to depart from this care model [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on patients seeking care in DSCs have focused on the prevalence of specific medical conditions or have been adapted from consumer surveys used in other settings that do not address issues of quality and provider interaction [8,9,10,11,12]. The current pilot study is a retrospective analysis of the case disposition form at the Harvard School of Dental Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Артериальная гипертензия (АГ) является одним из самых распространенных заболеваний сердечно-сосудистой системы, которыми страдают от 20 до 30% взрослого населения [1,2]. Эта патология стоит на первом месте по заболеваемости, инвалидизации и смертности населения в экономически развитых странах, а 57% жителей планеты уходят из жизни из-за ишемической болезни сердца и других сердечных патологий.…”
unclassified